Hidrocarburos de petróleo, disueltos y dispersos, en cuatro ambientes costeros de Costa Rica - Acuña-González, Jenaro (2004)
Four coastal ecosystems with contrasting characteristics were sampled in Costa Rica (2000 – 2002). Oil pollution status, expressed as the fraction of dissolved/dispersed petroleum hydrocarbons related to chrysene equivalents, was determined by the molecular fluorescence analytical technique. A total of 130 water samples were taken, from the Caribbean (Moín Bay), and from the Pacific (Bahía Culebra, Gulf of Nicoya and Dulce Gulf). On one occasion, seven samples along the Puntarenas estuary were also analysed. In Moín the mean and standard deviation were 0.10 μg·L-1 ± 0.18 μg·L-1, ranging from non detectable (nd) to 0.65 μg·L-1. For the Pacific ecosystems the total range was from nd to 0.37 μg·L-1. In Bahía Culebra no fluorescence signals were obtained. In the Gulf of Nicoya the mean and standard deviation were 0.04 μg·L-1 ± 0.09 μg·L-1, from nd to 0.33 μg·L-1. Values in Dulce Gulf were 0.05 μg·L-1 ± 0.11 μg·L-1, from nd to 0.37 μg·L-1. Along the Puntarenas estuary the range was 0.17 to 5.91 μg·L-1, with a mean of 1.21 μg·L-1 and a standard deviation of ± 2.10 μg·L-1. The four coastal ecosystems had concentrations below the 10 μg·L-1 limit for polluted oceanic areas. The Puntarenas estuary reflects the influence of